Comparison of RPR and ELISA with TPHA for the Diagnosis of Syphilis: Implication for Updating Syphilis Point-of-Care Tests in Ethiopia. (8th July 2018) - Negash, Markos; Wondmagegn, Tadelo; Geremew, Demeke
Abstract : Background. Syphilis is a sexually transmitted disease (STD) caused by the spirochete Treponema pallidum, and it persists to be a major public health problem in Africa, including Ethiopia. Syphilis diagnosis is made by either nontreponemal or treponemal approaches, though in developing countries the diagnosis relies mostly on nonspecific tests due to several reasons. Thus, the objective of this study was to assess the sensitivity, specificity, predictive values, and agreement of rapid plasma reagin (RPR) and enzyme-linked immunosorbent assay (ELISA) with Treponema pallidum hemagglutination assay (TPHA) as a gold standard for the diagnosis of syphilis. Results . The sensitivity, specificity, and positive and negative predictive values of ECOTEST-RPR were 100%, 80.8%, 76.2%, and 100%, respectively. However, the sensitivity, specificity, and positive and negative predictive values of DIALAB-ELISA were 98.4%, 94.9%, 92.3%, and 98.9%, respectively. The agreement between DIALAB-ELISA and Randox-TPHA was excellent (kappa value: 0.96) as compared to ECOTEST-RPR and Randox-TPHA assay (kappa value: 0.88). Conclusion. We found a characteristically variable performance of DIALAB-ELISA test and the currently available traditional ECOTEST-RPR test in the study area. The use of ECOTEST-RPR as a diagnostic test is confronted by its false positivity. Thus, neither the ECOTEST-RPR nor the DIALAB-ELISA test stands on its own to be used either as screening or confirmatory test for syphilis diagnosis. Consequently, thorough studies should be conducted aiming on a change of the current diagnostic scheme in the community.